The Effectiveness of a Post-Secondary Readiness Intervention in Increasing Students' Academic Preparation Knowledge: Self Efficacy as a Predictive Factor - Bieno, Glenna A. (My University, 2013)
Students least likely to attend college are first-generation students, ethnic- minority students, and students from low socio-economic statuses (SES). Although there is an abundance of research indicating that adequate academic preparation is a critical component of college planning, few studies have examined the effectiveness of college readiness intervention programs in increasing academic preparation knowledge (APK). In addition to APK, adolescents' self-efficacy can play a role in academic performance and college enrollment decisions. The current study examined the effectiveness of a college readiness program (Blugold Beginnings) in increasing middle school students' APK. A second aim of the current study was to examine the relationship between students' self- efficacy and students' APK gain over the course of the intervention. The Blugold Beginnings program is designed to increase subsequent college enrollment among low- income, first-generation, and ethnic minority students in grades 5-12. The findings suggested that participants' APK increased significantly as a result of participation in the program, although self-efficacy was not found to be related to participants' APK gain. The current study provides important contributions to the existing literature regarding the effectiveness of college readiness programs.
Keywords: Remedial teaching -- Evaluation; Academic achievement -- Psychological aspects; College preparation programs -- Evaluation; Self-efficacy -- Educational aspects; College preparation programs -- Wisconsin -- Eau Claire; Blugold Beginnings (Eau Claire, Wis.)